MODEL PEMBELAJARAN MAGANG BAGI JURNALISTIK FOTO OLAHRAGA DI MEDIA ONLINE - Kusumadinata, Ali; Ernawati, Erna; Sumah, Astrid Sri Wahyuni; Arrafi, Muhammad Daffa Fahdrizq Islam (JURNAL KAJIAN ISLAM MODERN, 2025)
The Internship learning model is part of one of the learning techniques that presents experiences to students personally or in groups accompanied by tutors or trainers. Internship-based learning activities have a good impact and contribute to developing new knowledge and deepening the expertise of students. This research activity aims to see the internship learning model in educating the professionalism of students or students in the field of journalism, especially in the field of photography. The method is carried out with qualitative descriptive by developing the concept of internships carried out in an input-process-output manner. The project-based learning technique is used in a participatory approach to work. The participants who were supervised in this case were 3 students with internships in online news Bola.com The results obtained were that the media activity was carried out almost 24 hours in capturing news and broadcasting it with attractive packaging, both in language and images. The news packaging is adjusted to the editorial issues that are conceptualized in one phenomenon of events. Daily activities in the media office include writing news, features, and opinion articles in the form of print media, electronic media, and online media. Journalism is closely related to journalism and mass media or media communication, press, and broadcasting (radio and television). The activities in the internship activities carried out are exploring and sharing sports information provided through a photo along with a caption which is the result of a sports photojournalist. A photo along with an informative caption is a very common thing for life. A photo or image that conveys certain information to make it more interesting and closer to the actual conditions.